'Horny and wanting to watch something': an exploratory qualitative analysis of heterosexual men's pornography viewing preferences. Issue 2 (3rd April 2022) - Sharkey, Matthew J.; Currin, Joseph M.; Cox, Kassidy; Golden, Brittney L.; Evans, Amelia E.; Garos, Sheila
ABSTRACT: The current study qualitatively explores the pornography viewing preferences of a non-university-based male sample from the United States. Cisgender heterosexual men ( N = 34) completed an online structured interview about their viewing preferences of pornographic material. Responses were grouped into two main categories, motivations to view pornography and viewing preferences. Unlike some previous pornography studies, a wide range of preferences for sexual activity was shared by the participants. The current study replicates findings from previous research and adds to the literature on male viewing preferences of pornography by highlighting several unique themes that emerged from the sample, including the reticence of heterosexual men to disclose having preferences for male actor characteristics and men viewing pornography to alter their current mental states.